Proceedings of the “Bioinformatics of African Diseases and Pathogen Vectors” Conference (Nairobi 2007) - Editorial - (:unkn) unknown (My University, 2009)
This special issue of Infection, Genetics and Evolution is devoted to the Bioinformatics of African Pathogens and Vectors conference, which was held in Nairobi (Kenya), 28th May-2nd June 2007.
Keywords: African Research